Benefits of genetic data for spatial conservation planning in coastal habitats - Andrello, Marco; Manel, Stéphanie; Vilcot, Maurine; Xuereb, Amanda; D’Aloia, Cassidy C. (Cambridge Prisms: Coastal Futures, 2023)
Coastal marine environments are subject to a variety of anthropogenic pressures that can negatively impact habitats and the biodiversity they harbor. Conservation actions such as marine protected areas, marine reserves, and other effective area-based conservation measures, are pivotal tools for protecting coastal biodiversity. However, to be effective, conservation area networks must be planned through a systematic conservation planning (SCP) approach. Recently, such approaches have begun to orient their goals toward the conservation of different biodiversity facets and to integrate different types of data. In this review, we illustrate how genetic data and molecular techniques can bring useful knowledge for SCP approaches that are both more comprehensive (sampling the full range of biodiversity) and more adequate (ensuring the long-term persistence of biodiversity). With an emphasis on coastal organisms and habitats, we focus on phylogenetic analysis, the estimation of neutral and adaptive intraspecific genetic diversity at different spatial levels (alpha, beta, and gamma), the study of connectivity and dispersal, and the information obtainable from environmental DNA techniques. For each of these applications, we discuss the benefits of its integration into SCP for coastal systems, its strengths and weaknesses, and the aspects yet to be developed.